(1)若2a-3b=4,则2a-(3b+3)=?(2)26°+49′16″+6°33′50″=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 11:28:40
(1)若2a-3b=4,则2a-(3b+3)=?(2)26°+49′16″+6°33′50″=?(1)若2a-3b=4,则2a-(3b+3)=?(2)26°+49′16″+6°33′50″=?(1)若
(1)若2a-3b=4,则2a-(3b+3)=?(2)26°+49′16″+6°33′50″=?
(1)若2a-3b=4,则2a-(3b+3)=?(2)26°+49′16″+6°33′50″=?
(1)若2a-3b=4,则2a-(3b+3)=?(2)26°+49′16″+6°33′50″=?
原式=2a-3b-3
=4-3
=1
原式=(26+6)°(49+33)'(16+50)''
=31°82'66'
=32°23'6'
(1)若2a-3b=4,则2a-(3b+3)=1
=2a-3b-3
=(2a-3b)-3
=4-3
=1
(2)26°+49′16″+6°33′50″=33°23'6''
=32°82'66''
=32°83'6'
=33°23'6''